Sustainable Tourism Management for Enhanced Tourism Product Quality in the Cultural Village of Dokan - Sitorus, Nova Bernedeta; Liyushiana, Liyushiana; Khairi, Nurhafizhah (LPPM Institut Pendidikan Nusantara Global, 2024)
The research on